The legal responsibility genesis as an institution of the law theory (historical and theoretical analysis) - Turlayev, A.V.; Volgina, A.P.; Morozov, N.V. (Bulletin of the Karaganda University “Law Series”, 2020)
The article describes the conception process and legal responsibility development as a category of law theories, discusses the main features of this institution. Historical retrospective describes the variability and progressive development of the responsibility institution is revealed in the punishment concept as an integral part of legal responsibility. The purpose of study concludes in identifying the main signs of legal responsibility and the development stages of this institution in different historical eras. Using general and special research methods, the analysis and synthesis of historical material, the various types consideration of legal responsibility in order to identify the basic laws of this institution development are carried out. The study result is the implementation development of the legal responsibility institute, the axiological aspects considering legal responsibility and the main patterns identification institute under study development. Legal liability is considered as a legal category, which legal punishments and rewards determines certain types, relations principles between the parties in criminal, administrative civil and other legal relations. The article concludes that the legal responsibility institute is in constant development, substantiates the position that in the twentieth century the modern legal responsibility principles are formed, the axiological basis of which is determined by humanism.